Practical theology and the call for the decolonisation of higher education in South Africa: Reflections and proposals - Dreyer, J. S. (HTS teologiese studies, 2017)
Although the issue of transformation has always been on the agenda of higher education since the transition to a democratic government in 1994, it is only since the student protests in 2015 and 2016 that the call for decolonisation of higher education in South Africa attracted much attention. The aim of this article is to reflect on the discipline of practical theology in South Africa in view of this call for decolonisation. Looking through the theoretical lens of decolonial theory, the author opts for an epistemological perspective on decolonisation. More particularly, the call for decolonisation of knowledge implies a struggle for epistemic justice. With this understanding of the call for decolonisation, the author reflects on the situation of practical theology in South Africa. The article concludes with three proposals for the decolonisation of practical theological research.